2022
DOI: 10.1039/d1ma01075a
|View full text |Cite
|
Sign up to set email alerts
|

CsPbI3 perovskite quantum dot solar cells: opportunities, progress and challenges

Abstract: Due to rapid increase in population, total electricity demands have been quickly rising. Under this circumstance, renewable energy technologies such as photovoltaic (PV) materials need to be urgently developed. Among...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 204 publications
0
14
0
Order By: Relevance
“…[6,187,188] Recently, the use of ligand-protected colloidal LHP NCs, especially CsPbI 3 and FAPbI 3 NCs, as photosensitizers has received increasing attention in the fabrication of PSCs with improved stability under long-term device operation. [14,47,61,62,160,[189][190][191][192][193][194] Importantly, it has been found that the LHP NC-based solar cells exhibit higher open-circuit voltage (V OC ) compared to their thin-film photovoltaics. [61,195] This was attributed to the reduced non-radiative recombination in perovskite NC solar cells and thus leading to smaller V OC losses relative to their bulk counterparts.…”
Section: Mixed A-cation Lhp Nc-based Solar Cellsmentioning
confidence: 99%
“…[6,187,188] Recently, the use of ligand-protected colloidal LHP NCs, especially CsPbI 3 and FAPbI 3 NCs, as photosensitizers has received increasing attention in the fabrication of PSCs with improved stability under long-term device operation. [14,47,61,62,160,[189][190][191][192][193][194] Importantly, it has been found that the LHP NC-based solar cells exhibit higher open-circuit voltage (V OC ) compared to their thin-film photovoltaics. [61,195] This was attributed to the reduced non-radiative recombination in perovskite NC solar cells and thus leading to smaller V OC losses relative to their bulk counterparts.…”
Section: Mixed A-cation Lhp Nc-based Solar Cellsmentioning
confidence: 99%
“…Perovskite quantum dots (PQDs) have captured an innovative impression that is exploited to improve the photovoltaic performance of numerous kinds of solar cells and summarized some challenges and perspectives concerning of PQDs [60]. The latest innovations in perovskite technology via diverse schemes, such as the amplify its functionality of methodological procedures, surface amendments, and solid QD inks near the device manner engineering for accomplishing sophisticated PV efficiency and enhanced longstanding steadiness [61]. Quantum dots (QDs) make available a multipurpose component to aid the most precise investigative tools and fluoroimmunoassays, dual imaging, multiplexed imaging, therapeutic platforms, real-time in vivo and cellular process imaging, and so on.…”
Section: Recent Automated Advancements In Quantum Dots For Multifunct...mentioning
confidence: 99%
“…Cesium lead halide (CsPbX 3 ) perovskite nanocrystals (NCs) are widely applied in the fields of solar cells, photodetectors, liquid crystal televisions, and other optoelectronics due to their high photoluminescence quantum yields (PLQYs), , narrow spectral widths, tunable PL spectrum in the whole visible light region, adjustable band gaps, and high color purity. In addition, low-dimensional perovskite NCs have been continuously studied. , However, the surface ligands of these NCs are easily desorbed during the purification process, resulting in the aggregation and growth of NCs into large particles, which decreases the stability and PLQYs . In particular, cesium lead iodide (CsPbI 3 ) NCs can accelerate degradation under the conditions of water, heat, and strong light.…”
Section: Introductionmentioning
confidence: 99%